Examining customer-oriented positive deviance intentions of retail employees. Issue 8 (17th July 2019) - Fazel-e-Hasan, Syed Muhammad; Mortimer, Gary; Lings, Ian; Drennan, Judy
Abstract : Purpose: Occasionally, retail employees "break the rules" in order to help customers. Currently, there is little research on the mechanisms by which a sales assistants' positive deviance intentions help them attain specific personal and organisational goals. The purpose of this paper is to examine one mechanism, hope, which develops employees' deviance intentions to provide benefits to the customer, themselves and the organisation. Design/methodology/approach: A survey captured responses from 270 frontline employees from the retail and services sector. AMOS 23 was used to conduct measurement, path and mediation analyses. Findings: This study highlights the role of employee hope in developing employees' positive deviance intentions, and improving perceptions of organisational performance. Results demonstrate that the direct positive impact of hope on positive deviance intention was significant. Furthermore, positive deviance intention was found to positively impact employee goal attainment and perceived organisational performance. The authors' employee hope model offers a better understanding of positive outcomes of employee deviance, suggesting that retail managers should invest resources to build strong employee–organisation relationships. Originality/value: This is the first study to empirically demonstrate that employee hope can explain how customer-oriented positive deviance intentions help employee goal attainment and improve their perceptions of organisational performance.